2018
DOI: 10.2147/ijn.s182428
|View full text |Cite
|
Sign up to set email alerts
|

Lipid surface modifications increase mesoporous silica nanoparticle labeling properties in mesenchymal stem cells

Abstract: BackgroundNanoparticles have emerged as promising cell-labeling tools, as they can be precisely tailored in terms of chemical and physical properties. Mesoporous silica nanoparticles (MSNs), in particular, are easily tunable with regard to surface and core chemistry, and are able to confine dyes and drug molecules efficiently.PurposeThe aim of this study was to investigate the effect of lipid and polyethylene glycol (PEG) surface modifications on MSN stem-cell-tracking abilities.MethodsLipid and PEG surface fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…3A and S2, right) in hMSCs cultured on the MSN films compared to those exposed to the colloidal calcein loaded MSN suspension. The uptake of calcein by hMSCs when adding MSNs in suspension was stable over 2 d, consistent with previous findings that MSNs in suspensions are internalized in hMSCs within the first few hours of culture [31].…”
Section: Msn Films Can Deliver Biomolecules To Instruct Stem Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…3A and S2, right) in hMSCs cultured on the MSN films compared to those exposed to the colloidal calcein loaded MSN suspension. The uptake of calcein by hMSCs when adding MSNs in suspension was stable over 2 d, consistent with previous findings that MSNs in suspensions are internalized in hMSCs within the first few hours of culture [31].…”
Section: Msn Films Can Deliver Biomolecules To Instruct Stem Cellssupporting
confidence: 90%
“…Since the in vitro differentiation of hMSCs towards an adult lineage relies on continuous presence of bioactive molecules, we pursued the possibility of using lipid bilayer surface functionalization to slow down cargo release. The lipid surface modification has been used by us and others to create biocompatible MSNs that allow sustained cargo release by blocking the MSN pores [23,26,31]. Indeed, we could show that using a lipid bilayer, calcein delivery was significantly slowed down; both from the films and when hMSCs were cultured on MSN-DOPC films.…”
Section: Discussionmentioning
confidence: 90%
“…For proteomics experiments, liver homogenates were used (n=3 for each group of mice). The samples were prepared as described previously (26). Briefly, proteins were extracted, reduced with 20 mM dithiothreitol for 45 minutes and alkylated with 40 mM iodoacetamide for 45 minutes in the dark.…”
Section: Label-free Lc-ms (Liquid Chromatography Mass Spectrometry) Based Proteomicsmentioning
confidence: 99%
“…The search engine Sequest was used with the Swiss-Prot mouse database (Mus musculus, TaxID 10090). The settings for the database search were similar as before (26). Proteins with a falsediscovery rate ≤ 1% were considered for the analysis and were normalized to the total peptide amount.…”
Section: Label-free Lc-ms (Liquid Chromatography Mass Spectrometry) Based Proteomicsmentioning
confidence: 99%
“…The in vivo tracking of transplanted stem cells allows a guided and more precise therapy. Rosenbrand et al showed that modifications of MSNs with lipids and PEG can improve their ability for stem-cell tracking by increasing the labeling efficiency and signal intensity [ 319 ]. Kempen et al synthesized MSNs to serve as both drug carriers and labeling agents for ultrasound and MRI [ 320 ].…”
Section: Update On Msn Applications In Nanomedicinesmentioning
confidence: 99%